Liver sinusoidal endothelial cells regulate the balance between hepatic immunosuppression and immunosurveillance - Kremer, Kimberly N.; Khammash, Hadeel A.; Miranda, Anjelica M.; Rutt, Lauren N.; Twardy, Shannon M.; Anton, Paige E.; Campbell, Margaret L.; Garza-Ortiz, Christian; Orlicky, David J.; Pelanda, Roberta; McCullough, Rebecca L.; Torres, Raul M. (Frontiers in Immunology, 2025)
As a metabolic center, the liver prevents inappropriate immune responses to abundant dietary antigens within the liver that could result in liver injury. This self-preservation mechanism can however decrease the efficiency of immunosurveillance of malignant cells by CD8 T cells. Hepatocellular carcinoma (HCC) is initiated by chronic viral infections, chronic alcohol consumption, and/or a fatty diet that leads to liver injury, fibrosis, and cirrhosis. HCC patients have high levels of dysfunctional and exhausted T cells, however, it is unclear which stage of HCC development contributes to T cell dysfunction. Repair of liver injury is initiated by interactions between injured hepatocytes and liver sinusoidal endothelial cells (LSEC), however, chronic injury can lead to fibrosis. Here, using a diethylnitrosamine/carbon tetrachloride (DEN/CCl4) mouse model of early HCC development, we demonstrate that chronic liver injury and fibrosis are sufficient to induce a CD8 T cell exhaustion signature with a corresponding increase in expression of immunosuppressive molecules on LSEC. We show that LSEC alter T cell function at various stages of T cell differentiation/activation. LSEC compete with dendritic cells presenting the same antigen to naïve CD8 T cells resulting in a unique T cell phenotype. Furthermore, LSEC abrogate killing of target cells, in an antigen-dependent manner, by previously activated effector CD8 T cells, and LSEC change the effector cell cytokine profile. Moreover, LSEC induce functional T cell exhaustion under low dose chronic stimulation conditions. Thus, LSEC critically regulate the balance between preventing/limiting liver injury and permitting sufficient tumor immunosurveillance with normal hepatic functions likely contributing to HCC development under conditions of chronic liver insult.